Bi-Quadratic Varying Deceleration Parameter to Study the Cosmological Model. Issue 1 (1st May 2022) - Kumar, R; Arora, S
Abstract: This paper investigates a cosmological model employing a four-degree function of cosmic time t in the f(R, T) gravity theory using an extended form of deceleration parameter. Under the constraints of flat, diagonal, and Bianchi type-1 metrics, we develop the exact solution of Einstein field equations (EFE). We research early time deceleration and accomplish the definite solution of EFE using an extended form of deceleration parameter, as well as the always super-exponential expansion behaviour of bi-quadratically variable deceleration parameter using a graph. We explore the model's efficacy by examining the relationship between the deceleration parameter and red shift, which offers a valid result concerning the FRW metric's consistent homogeneous structure in light of recent cosmological observations.